2021
DOI: 10.1016/s2214-109x(21)00045-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a host blood transcriptomic biomarker for pulmonary tuberculosis in people living with HIV: a prospective diagnostic and prognostic accuracy study

Abstract: Background A rapid, blood-based triage test that allows targeted investigation for tuberculosis at the point of care could shorten the time to tuberculosis treatment and reduce mortality. We aimed to test the performance of a host blood transcriptomic signature (RISK11) in diagnosing tuberculosis and predicting progression to active pulmonary disease (prognosis) in people with HIV in a community setting.Methods In this prospective diagnostic and prognostic accuracy study, adults (aged 18-59 years) with HIV wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Our data suggest that intercurrent respiratory viral infections, such as rhinovirus and coronavirus, drive signature conversion and transient positive TB risk status. It is also clear that HIV infection elevates RISK11 signature scores, as reported previously ( 12 , 17 ). A recent study of healthy TB-exposed individuals living in a TB-endemic setting demonstrated that the majority had detectable Mtb DNA in peripheral blood leukocytes ( 18 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data suggest that intercurrent respiratory viral infections, such as rhinovirus and coronavirus, drive signature conversion and transient positive TB risk status. It is also clear that HIV infection elevates RISK11 signature scores, as reported previously ( 12 , 17 ). A recent study of healthy TB-exposed individuals living in a TB-endemic setting demonstrated that the majority had detectable Mtb DNA in peripheral blood leukocytes ( 18 ).…”
Section: Discussionsupporting
confidence: 83%
“…We enrolled HIV-uninfected volunteers into two observational cohorts nested in the CORTIS (Correlate of Risk Targeted Intervention Study) trial ( 13 ) (ClinicalTrials.gov: NCT02735590) and HIV-infected volunteers into a cohort nested in the observational CORTIS-HR (Validation of Correlates of Risk of TB Disease in High Risk Populations) study ( 17 ), respectively ( Figure 1 ; Figure E1 in the online supplement). These three cohorts allowed evaluation of 1 ) transcriptomic signature dynamics in HIV-uninfected and HIV-infected individuals; 2 ) transcriptomic signature dynamics with and without TPT; and 3 ) effects of upper respiratory organisms on the transcriptomic signature.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the low amount of bacilli replication and the minimal lesions present at this stage, today it is still difficult to recommend an “ideal” drug regimen to treat incipient TB [ 27 , 28 ]. Future studies are needed to provide insights on the best clinical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several blood transcriptional signatures have been identified as potential predictors of development of incident disease [8,[10][11][12][13]. The performance of RISK11, an 11-gene transcriptomic host-response blood signature was recently evaluated in PLHIV in the CORTIS-HR study [14]. Amongst HIV-positive adults in South Africa, RISK11 was able to predict progression to TB in those without prevalent TB at baseline, with sensitivity of 88.6 (43.5-98.7) and specificity of 68.9 (65.3-72.3) over 15 months following screening, approaching the TPP minimum benchmarks.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we use a mathematical model, informed by data from the Correlate of Risk Targeted Intervention Study in High Risk Populations (CORTIS-HR) [14,15], to simulate different strategies for transcriptomic targeted preventive therapy amongst PLHIV. Specifically, we explore whether repeat transcriptomic screening followed by short-course preventive therapy may reduce incidence of TB amongst PLHIV compared to universal provision of preventive therapy in PLHIV as recommend by WHO.…”
Section: Introductionmentioning
confidence: 99%